2007
DOI: 10.1111/j.0030-1299.2007.15521.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of crypsis in replicating populations of web‐based prey

Abstract: To investigate the evolution of background matching (crypsis) when prey are viewed against uniform and heterogeneous (alternating) backgrounds, we conducted some web-based experiments. Visitors to our experimental web site were rewarded for finding artificial prey, thereby providing a measure of their detectability. We first compared the ''survivorship'' of a range of pixilated prey phenotypes presented against both light green and dark green pixilated backgrounds and found clear evidence for a concave tradeof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 27 publications
3
40
0
Order By: Relevance
“…by having a coloration adapted to one particular patch type or by having a compromised coloration adapted to several patch types Distractive markings conceal prey M. Dimitrova et al 1909(Merilaita et al 1999Houston et al 2007;Sherratt et al 2007). Our results can be interpreted from this point of view as well.…”
Section: Discussionmentioning
confidence: 49%
“…by having a coloration adapted to one particular patch type or by having a compromised coloration adapted to several patch types Distractive markings conceal prey M. Dimitrova et al 1909(Merilaita et al 1999Houston et al 2007;Sherratt et al 2007). Our results can be interpreted from this point of view as well.…”
Section: Discussionmentioning
confidence: 49%
“…First, matching a random sample of the background does not necessarily minimize the risk of detection when an animal is found on several backgrounds (cf. 'compromise camouflage'; Merilaita et al 1999Merilaita et al , 2001Houston et al 2007;Sherratt et al 2007). Second, the risk of detection can be decreased by disruptive markings, where the emphasis is on specifically breaking up tell-tale features of the animal.…”
Section: (B) What Is 'Crypsis'?mentioning
confidence: 99%
“…Human predators have frequently been used by researchers in studies of crypsis (e.g. Tucker & Allen 1993;Knill & Allen 1995;Glanville & Allen 1997;Sherratt et al 2007) and good qualitative concordance has been found between the performances of birds and humans when conducting simple discriminative tasks (e.g. Dittrich et al 1993;Beatty et al 2005).…”
Section: Introductionmentioning
confidence: 99%